Sigma elements are position-specific for many different yeast tRNA genes. - Sandmeyer, S B (1988)
We determined the DNA sequence of seventeen sigma elements and flanking regions in order to investigate the extent of the association between the yeast repetitive element, sigma, and tRNA genes. Fifteen of seventeen sigma elements analyzed begin at position -19 to -16 with respect to the 5' end of a tRNA-coding sequence. This region is close to the initiation point of tRNA gene transcription and contains a sequence which is modestly conserved for a number of tRNA genes. Two pairs of identical sigma elements occur as the long terminal repeats of a sequence which, together with flanking sigma elements, has the structural properties of a retrotransposon; this element has been named Ty3 (manuscript submitted). Hybridization analysis of yeast chromosomal DNA separated by orthogonal field alternation gel electrophoresis (OFAGE) showed that Ty3 and isolated sigma elements are distributed over many chromosomes in the yeast genome.